Novel Co-processed Spray Dried Super Disintegrants Designing of Fast Dissolving Tablets Using - Shirsand, SB; Gumate, RT; Jonathan, V; Shailashri, - (Dhaka University Journal of Pharmaceutical Sciences, 2017)
In the present study, novel co-processed superdisintegrants were developed by spray drying method using microcrystalline cellulose and mannitol in different ratios (1:1, 1:2 and 1:3) for use in the fast dissolving tablet formulations. The developed excipients were evaluated for angle of repose, Carrs index and Hausners ratio in comparison with physical mixture of superdisintegrants. The angle of repose of the developed excipients was found to be < 30o, Carrs index in the range of 9-15 % and Hausners ratio in the range of 1.12-1.16. Fast dissolving tablets of glibenclamide were prepared using the above co-processed superdisintegrants and evaluated for pre-compression and post-compression parameters. Based on in vitro dispersion time (approximately 22.23 sec), promising formulation MCM3 was tested for in vitro drug release pattern in pH 6.8 phosphate buffer and stability (at 400C/75 % RH for 3 months), drug excipients interaction (IR spectroscopy) were studied. Among the designed formulations, the formulation (MCM3) containing 8 % w/w of co-processed superdisintegrant (1:3 mixture of microcrystalline cellulose and mannitol) emerged as the overall best formulation (t50% 1.6 min) based on drug release characteristics in pH 6.8 phosphate buffer compared to commercial conventional tablet formulation (t50% 6 min). Stability studies on promising formulation indicated that there were no significant changes in drug content and in vitro dispersion time (p<0.05). Dhaka Univ. J. Pharm. Sci. 15(2): 167-172, 2016 (December)